2017
DOI: 10.5811/westjem.2017.5.33543
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physician-performed Transesophageal Echocardiography in Simulated Cardiac Arrest

Abstract: IntroductionTransesophageal echocardiography (TEE) is a well-established method of evaluating cardiac pathology. It has many advantages over transthoracic echocardiography (TTE), including the ability to image the heart during active cardiopulmonary resuscitation. This prospective simulation study aims to evaluate the ability of emergency medicine (EM) residents to learn TEE image acquisition techniques and demonstrate those techniques to identify common pathologic causes of cardiac arrest.MethodsThis was a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…Our literature review indicated that the only published mention of training in the use of TEE in emergency departments and ICUs involved small sample groups . We did not find any comparisons of teaching methods.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our literature review indicated that the only published mention of training in the use of TEE in emergency departments and ICUs involved small sample groups . We did not find any comparisons of teaching methods.…”
Section: Discussionmentioning
confidence: 71%
“…Our literature review indicated that the only published mention of training in the use of TEE in emergency departments and ICUs involved small sample groups. 34,35 We did not find any comparisons of teaching methods. Ample populations and diverse physician specialists are needed to determine the effectiveness of TEE during resuscitation from cardiac arrest as well as the most effective teaching methods.…”
Section: Use Of Transesophageal Echocardiography In the Emergency Depmentioning
confidence: 85%
“…To the best of our knowledge, this is the first scoping review that eval- ) 7,69 to more advanced applications (such as transesophageal echocardiogram) 33,38,41,83,84 and clinical integration of skills with protocols and algorithms (such as undifferentiated hypotension). 67,81,108,109,123,124,131 There is also strong evidence on the remarkable innovations that showcase emergency ultrasound education over this period.…”
Section: Discussionmentioning
confidence: 99%
“…10,14 Emergency medicine residents have used TEE in simulated arrest scenarios with a high degree of precision and accuracy. 15 Simplified three-view protocols succinctly direct emergency physicians. 10 After undergoing successful aortic reconstruction, the patient was extubated the next day.…”
Section: Discussionmentioning
confidence: 99%